Introduction. - McCants, Anne E. C.; Zilberstein, Anya (Journal of Interdisciplinary History)
This article discusses the field of interdisciplinary history and its relationship with the natural sciences. It highlights the contributions of historian Harriet Ritvo, particularly in the areas of animal history, environmental history, and the history of science. The article emphasizes the importance of breaking down the boundaries between human and non-human actors in historical research and challenges the anthropocentric perspective that has traditionally dominated the discipline. The essays in this special issue explore various aspects of Ritvo's work and its implications for understanding the complex relationships between humans and the natural world. The article concludes by urging historians to engage more with the natural sciences and to consider the historical context in which scientific knowledge is produced.